T cell receptor repertoires after adoptive transfer of expanded allogeneic regulatory T cells. (27th November 2016) - Theil, A.; Wilhelm, C.; Kuhn, M.; Petzold, A.; Tuve, S.; Oelschlägel, U.; Dahl, A.; Bornhäuser, M.; Bonifacio, E.; Eugster, A.
Summary: Regulatory T cell (Treg ) therapy has been exploited in autoimmune disease, solid organ transplantation and in efforts to prevent or treat graft‐ versus ‐host disease (GVHD). However, our knowledge on the in‐vivo persistence of transfused Treg is limited. Whether Treg transfusion leads to notable changes in the overall Treg repertoire or whether longevity of Treg in the periphery is restricted to certain clones is unknown. Here we use T cell receptor alpha chain sequencing (TCR‐α‐NGS) to monitor changes in the repertoire of Treg upon polyclonal expansion and after subsequent adoptive transfer. We applied TCR‐α‐NGS to samples from two patients with chronic GVHD who received comparable doses of stem cell donor derived expanded Treg . We found that in‐vitro polyclonal expansion led to notable repertoire changes in vitro and that Treg cell therapy altered the peripheral Treg repertoire considerably towards that of the infused cell product, to different degrees, in each patient. Clonal changes in the peripheral blood were transient and correlated well with the clinical parameters. We suggest that T cell clonotype analyses using TCR sequencing should be considered as a means to monitor longevity and fate of adoptively transferred T cells. Abstract : T cell receptor sequencing was exploited as a method to monitor changes in the repertoire of regulatory T cells (Treg) after allogeneic Treg cell therapy in two patients with chronic graft‐versus‐host disease. Polyclonal expansion led to notable repertoire changes of the cell product pre transfer. Infusion of expanded Treg notably altered peripheral Treg repertoires toward that of the cell product, to different degrees in individual paitents.